Hydrothermal-derived carbon as a stabilizing matrix for improved cycling performance of silicon-based anodes for lithium-ion full cells - Ruttert, Mirco; Holtstiege, Florian; Hüsker, Jessica; Börner, Markus; Winter, Martin; Placke, Tobias (Beilstein Journal of Nanotechnology, 2018)
In this work, silicon/carbon composites are synthesized by forming an amorphous carbon matrix around silicon nanoparticles (Si-NPs) in a hydrothermal process. The intention of this material design is to combine the beneficial properties of carbon and Si, i.e., an improved specific/volumetric capacity and capacity retention compared to the single materials when applied as a negative electrode in lithium-ion batteries (LIBs). This work focuses on the influence of the Si content (up to 20 wt %) on the electrochemical performance, on the morphology and structure of the composite materials, as well as the resilience of the hydrothermal carbon against the volumetric changes of Si, in order to examine the opportunities and limitations of the applied matrix approach. Compared to a physical mixture of Si-NPs and the pure carbon matrix, the synthesized composites show a strong improvement in long-term cycling performance (capacity retention after 103 cycles: ≈55% (20 wt % Si composite) and ≈75% (10 wt % Si composite)), indicating that a homogeneous embedding of Si into the amorphous carbon matrix has a highly beneficial effect. The most promising Si/C composite is also studied in a LIB full cell vs a NMC-111 cathode; such a configuration is very seldom reported in the literature. More specifically, the influence of electrochemical prelithiation on the cycling performance in this full cell set-up is studied and compared to non-prelithiated full cells. While prelithiation is able to remarkably enhance the initial capacity of the full cell by ≈18 mAh g−1, this effect diminishes with continued cycling and only a slightly enhanced capacity of ≈5 mAh g−1 is maintained after 150 cycles.
Keywords: LIB full cell; lithium-ion batteries; prelithiation; silicon/carbon composite; solid–electrolyte interphase (SEI)

(untitled) - Placke, T.; Kloepsch, R.; Dühnen, S.; Winter, M. (J. Solid State Electrochem., 2017)

(untitled) - Nitta, N.; Wu, F.; Lee, J. T.; Yushin, G. (Mater. Today, 2015)

(untitled) - Blomgren, G. E. (J. Electrochem. Soc., 2017)

(untitled) - Goodenough, J. B.; Park, K.-S. (J. Am. Chem. Soc., 2013)

(untitled) - Schmuch, R.; Wagner, R.; Hörpel, G.; Placke, T.; Winter, M. (Nat. Energy, 2018)

(untitled) - Chao, D.; Xia, X.; Liu, J.; Fan, Z.; Ng, C. F.; Lin, J.; Zhang, H.; Shen, Z. X.; Fan, H. J. (Adv. Mater., 2014)

Handbook of Battery Materials - Winter, M.; Besenhard, J. O. (Lithiated Carbons, 2011)

(untitled) - Meister, P.; Jia, H.; Li, J.; Kloepsch, R.; Winter, M.; Placke, T. (Chem. Mater., 2016)

(untitled) - Winter, M.; Besenhard, J. O.; Albering, J. H.; Yang, J.; Wachtler, M. (Prog. Batteries Battery Mater., 1998)

(untitled) - Obrovac, M. N.; Chevrier, V. L. (Chem. Rev., 2014)

(untitled) - Besenhard, J. O.; Yang, J.; Winter, M. (J. Power Sources, 1997)

(untitled) - Nitta, N.; Yushin, G. (Part. Part. Syst. Charact., 2014)

(untitled) - Obrovac, M. N.; Christensen, L. (Electrochem. Solid-State Lett., 2004)

(untitled) - Obrovac, M. N.; Krause, L. J. (J. Electrochem. Soc., 2007)

(untitled) - Kasavajjula, U.; Wang, C.; Appleby, A. J. (J. Power Sources, 2007)

(untitled) - Zuo, X.; Zhu, J.; Müller-Buschbaum, P.; Cheng, Y.-J. (Nano Energy, 2017)

(untitled) - Zhang, W.-J. (J. Power Sources, 2011)

(untitled) - Peled, E.; Menkin, S. (J. Electrochem. Soc., 2017)

(untitled) - Winter, M. (Z. Phys. Chem., 2009)

(untitled) - Schmitz, R. W.; Murmann, P.; Schmitz, R.; Müller, R.; Krämer, L.; Kasnatscheew, J.; Isken, P.; Niehoff, P.; Nowak, S.; Röschenthaler, G.-V.; Ignatiev, N.; Sartori, P.; et al. (Prog. Solid State Chem., 2014)

(untitled) - Winter, M.; Appel, W. K.; Evers, B.; Hodal, T.; Möller, K.-C.; Schneider, I.; Wachtler, M.; Wagner, M. R.; Wrodnigg, G. H.; Besenhard, J. O. (Monatsh. Chem., 2001)

(untitled) - Wachtler, M.; Besenhard, J. O.; Winter, M. (J. Power Sources, 2001)

(untitled) - Vogl, U. S.; Lux, S. F.; Das, P.; Weber, A.; Placke, T.; Kostecki, R.; Winter, M. (J. Electrochem. Soc., 2015)

(untitled) - Wu, H.; Cui, Y. (Nano Today, 2012)

(untitled) - Holtstiege, F.; Wilken, A.; Winter, M.; Placke, T. (Phys. Chem. Chem. Phys., 2017)

(untitled) - Wachtler, M.; Wagner, M. R.; Schmied, M.; Winter, M.; Besenhard, J. O. (J. Electroanal. Chem., 2001)

(untitled) - Reyes Jiménez, A.; Klöpsch, R.; Wagner, R.; Rodehorst, U. C.; Kolek, M.; Nölle, R.; Winter, M.; Placke, T. (ACS Nano, 2017)

(untitled) - Liu, X. H.; Zhong, L.; Huang, S.; Mao, S. X.; Zhu, T.; Huang, J. Y. (ACS Nano, 2012)

(untitled) - Szczech, J. R.; Jin, S. (Energy Environ. Sci., 2011)

(untitled) - Hochgatterer, N. S.; Schweiger, M. R.; Koller, S.; Raimann, P. R.; Wöhrle, T.; Wurm, C.; Winter, M. (Electrochem. Solid-State Lett., 2008)

(untitled) - Kwon, T.-w.; Choi, J. W.; Coskun, A. (Chem. Soc. Rev., 2018)

(untitled) - Han, Z.-J.; Yabuuchi, N.; Shimomura, K.; Murase, M.; Yui, H.; Komaba, S. (Energy Environ. Sci., 2012)

(untitled) - Vogl, U. S.; Das, P. K.; Weber, A. Z.; Winter, M.; Kostecki, R.; Lux, S. F. (Langmuir, 2014)

(untitled) - Nguyen, C. C.; Lucht, B. L. (J. Electrochem. Soc., 2014)

(untitled) - Etacheri, V.; Haik, O.; Goffer, Y.; Roberts, G. A.; Stefan, I. C.; Fasching, R.; Aurbach, D. (Langmuir, 2012)

(untitled) - Liu, W.-R.; Yen, Y.-C.; Wu, H.-C.; Winter, M.; Wu, N.-L. (J. Appl. Electrochem., 2009)

(untitled) - Shen, T.; Xia, X.-h.; Xie, D.; Yao, Z.-j.; Zhong, Y.; Zhan, J.-y.; Wang, D.-h.; Wu, J.-b.; Wang, X.-l.; Tu, J.-p. (J. Mater. Chem. A, 2017)

(untitled) - Liu, N.; Wu, H.; McDowell, M. T.; Yao, Y.; Wang, C.; Cui, Y. (Nano Lett., 2012)

(untitled) - Jia, H.; Stock, C.; Kloepsch, R.; He, X.; Badillo, J. P.; Fromm, O.; Vortmann, B.; Winter, M.; Placke, T. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Chen, Y.; Qian, J.; Cao, Y.; Yang, H.; Ai, X. (ACS Appl. Mater. Interfaces, 2012)

(untitled) - Demir Cakan, R.; Titirici, M.-M.; Antonietti, M.; Cui, G.; Maier, J.; Hu, Y.-S. (Chem. Commun., 2008)

(untitled) - Schmuelling, G.; Winter, M.; Placke, T. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Moriga, T.; Watanabe, K.; Tsuji, D.; Massaki, S.; Nakabayashi, I. (J. Solid State Chem., 2000)

(untitled) - Courtel, F. M.; Duguay, D.; Abu-Lebdeh, Y.; Davidson, I. J. (J. Power Sources, 2012)

(untitled) - Liu, W.-R.; Wu, N.-L.; Shieh, D.-T.; Wu, H.-C.; Yang, M.-H.; Korepp, C.; Besenhard, J. O.; Winter, M. (J. Electrochem. Soc., 2007)

(untitled) - Huang, Y.-H.; Bao, Q.; Duh, J.-G.; Chang, C.-T. (J. Mater. Chem. A, 2016)

(untitled) - Chou, S.-L.; Wang, J.-Z.; Choucair, M.; Liu, H.-K.; Stride, J. A.; Dou, S.-X. (Electrochem. Commun., 2010)

(untitled) - Xing, Y.; Shen, T.; Guo, T.; Wang, X.; Xia, X.; Gu, C.; Tu, J. (J. Power Sources, 2018)

(untitled) - Liu, Y.; Wen, Z. Y.; Wang, X. Y.; Yang, X. L.; Hirano, A.; Imanishi, N.; Takeda, Y. (J. Power Sources, 2009)

(untitled) - Dimov, N.; Kugino, S.; Yoshio, M. (Electrochim. Acta, 2003)

(untitled) - Lee, H.-Y.; Lee, S.-M. (Electrochem. Commun., 2004)

(untitled) - Wang, Q.; Li, H.; Chen, L.; Huang, X. (Carbon, 2001)

(untitled) - Hu, Y.-S.; Demir-Cakan, R.; Titirici, M.-M.; Müller, J.-O.; Schlögl, R.; Antonietti, M.; Maier, J. (Angew. Chem., Int. Ed., 2008)

(untitled) - Forney, M. W.; Ganter, M. J.; Staub, J. W.; Ridgley, R. D.; Landi, B. J. (Nano Lett., 2013)

(untitled) - Holtstiege, F.; Bärmann, P.; Nölle, R.; Winter, M.; Placke, T. (Batteries (Basel, Switz.), 2018)

(untitled) - Chevrier, V. L.; Liu, L.; Wohl, R.; Chandrasoma, A.; Vega, J. A.; Eberman, K. W.; Stegmaier, P.; Figgemeier, E. (J. Electrochem. Soc., 2018)

(untitled) - Marinaro, M.; Weinberger, M.; Wohlfahrt-Mehrens, M. (Electrochim. Acta, 2016)

(untitled) - Tien, B.; Xu, M.; Liu, J. (Mater. Lett., 2010)

(untitled) - Jin, Y. Z.; Gao, C.; Hsu, W. K.; Zhu, Y.; Huczko, A.; Bystrzejewski, M.; Roe, M.; Lee, C. Y.; Acquah, S.; Kroto, H.; Walton, D. R. (Carbon, 2005)

(untitled) - Kristianto, H.; Putra, C. D.; Arie, A. A.; Halim, M.; Lee, J. K. (Procedia Chem., 2015)

(untitled) - Nieto-Márquez, A.; Romero, R.; Romero, A.; Valverde, J. L. (J. Mater. Chem., 2011)

(untitled) - Xia, X.; Wang, Y.; Wang, D.; Zhang, Y.; Fan, Z.; Tu, J.; Zhang, H.; Fan, H. J. (Nano Energy, 2016)

(untitled) - Heckmann, A.; Meister, P.; Meyer, H. W.; Rohrbach, A.; Winter, M.; Placke, T. (ECS Trans., 2015)

(untitled) - Fromm, O.; Heckmann, A.; Rodehorst, U. C.; Frerichs, J.; Becker, D.; Winter, M.; Placke, T. (Carbon, 2018)

(untitled) - Heckmann, A.; Fromm, O.; Rodehorst, U.; Münster, P.; Winter, M.; Placke, T. (Carbon, 2018)

(untitled) - Freunberger, S. A. (Nat. Energy, 2017)

(untitled) - Krueger, S.; Kloepsch, R.; Li, J.; Nowak, S.; Passerini, S.; Winter, M. (J. Electrochem. Soc., 2013)

(untitled) - Kasnatscheew, J.; Placke, T.; Streipert, B.; Rothermel, S.; Wagner, R.; Meister, P.; Laskovic, I. C.; Winter, M. (J. Electrochem. Soc., 2017)

(untitled) - Kim, H. J.; Choi, S.; Lee, S. J.; Seo, M. W.; Lee, J. G.; Deniz, E.; Lee, Y. J.; Kim, E. K.; Choi, J. W. (Nano Lett., 2016)

(untitled) - Dreyer, W.; Jamnik, J.; Guhlke, C.; Huth, R.; Moškon, J.; Gaberšček, M. (Nat. Mater., 2010)

(untitled) - Beattie, S. D.; Loveridge, M. J.; Lain, M. J.; Ferrari, S.; Polzin, B. J.; Bhagat, R.; Dashwood, R. (J. Power Sources, 2016)